Upaya Pemerintah Desa Dalam Mengurangi Stigma Sosial Melalui Pemberdayaan Orang Dalam Gangguan Jiwa Di Desa Ngunut - Adelia Dwi Cahyani; Robby Darwis Nasution; Irvan Nur Ridho; Yusuf Adam Hilman (Jurnal Ilmu Pemerintahan, 2024)
Law No.18 of 2014 states that mental disorders are a collection of abnormal conditions, both physical and mental. The aim of this research is to describe and analyze the village government’s efforts to reduce social stigma through empowering people with mental disorders in Ngunut Village. This research uses a qualitative descriptive research type. To understand more deeply about a person’s condition, stigma can be reduced because society will be more likely to view them as individuals with unique experiences that require a special approach, not just stigma or negative stereotypes. Based on the discussion above, it can be concluded that mental health Posyandu always provides intensive care to people with mental disorders. This care takes the form of regular medication assistance, and they not only hand out prescriptions and medication, but they do everything they can to ensure that people who need mental health treatment take their medication consistently and regularly according to the doctor’s prescription. Posyandu provides support and education to the community and their families about the importance of regular medication intake to minimize the rizk of relapse and maintain mental stability. Mental health posyandu aims to increase treatment compliance with an approach that focuses on understanding and support so that people with mental health disorders can recover better